设函数 $f(x)=\frac{(x+1)^n}{\mathrm{e}^{x^2}}$, 则 $f^{(n)}(-1)=$
【答案】 $\frac{n !}{\mathrm{e}}$.


【解析】 由于 $f(x)=(x+1)^n \mathrm{e}^{-x^2}$, 由莱布尼茨公式得
$$
\begin{aligned}
f^{(n)}(x) &=\left[(x+1)^n \mathrm{e}^{-x^2}\right]^{(n)}=\sum_{k=0}^n \mathrm{C}_n^k\left[(x+1)^n\right]^{(k)}\left(\mathrm{e}^{-x^2}\right)^{(n-k)} \\
&=\sum_{k=0}^{n-1} \mathrm{C}_n^k\left[(x+1)^n\right]^{(k)}\left(\mathrm{e}^{-x^2}\right)^{(n-k)}+\mathrm{C}_n^n\left[(x+1)^n\right]^{(n)} \mathrm{e}^{-x^2} \\
&=\sum_{k=0}^{n-1} \mathrm{C}_n^k n(n-1) \cdots(n-k+1)(x+1)^{n-k}\left(\mathrm{e}^{-x^2}\right)^{(n-k)}+n ! \mathrm{e}^{-x^2},
\end{aligned}
$$
则 $f^{(n)}(-1)=\frac{n !}{\mathrm{e}}$.
系统推荐